Colonic Preparation with Manitol - Harretche, Martín; Veroli, Antonio; Armand Ugon, Alfredo (Cirugía del Uruguay, 1980)
Report on a method fór the preparation of colon bbefare surgery, radiology or endoscopy, This method, tested on a reduced number of cases, has proved its safety, ease of administration and good tollerance; there are neither complications ·nor counterindications. The procedure is economic and highly efficient and should be employed more widely.